Big Data and Lots of Data are Not the Same Things: Small data sources in the social science of archaeologists - Kenneth Aitchison (Internet Archaeology, 2024)
'Big Data' is a misunderstood but technically definable concept; it is large volume, unstructured, heterogenous information, that is being generated at a high velocity - which normally means it is being constantly updated in real time. And, in many situations, this is very difficult to work with; an analogy might be to compare the curated content of Netflix, which is a (very) large but structured data set, with the unending chaos of YouTube content, which is Big Data. The first part of this paper considers big data, and how it is defined and used, with the second part considering how large amounts of small data can be used in sociology as applied to archaeology.